(untitled) (Altre Modernità, 2025)
The essay provides a perspective of the Sicilian magazine Scorci, which was founded in 2021 and is still active today. Through an overview of the six monographic issues and a reading of the articles, its profile of ‘situated’ essayism is presented. The magazine’s cultural references are investigated, namely the Sicilian literary, cultural and filmic tradition, Danilo Dolci’s militant activity and the popular uprisings of XX century. Through an analysis of popular struggles, both the agrarian and workers’ in the 20th century, and the current ones against Muos or in favour of feminist demands, Scorci’s ‘varied humanity’ is presented in antithesis to both the neo-idealistic humanistic tradition and to the ‘lyrical Mediterraneanism’ of the early 2000s, represented by Franco Cassano, among others, and studied by Francescomaria Tedesco. The last part of the essay is dedicated to showcasing the variety of aesthetic-cultural topics covered by the journal and its views on war and the climate crisis, which, in terms of intellectual positioning, aim to overcome the dichotomy between the two cultures: humanistic and scientific.